2018
DOI: 10.4103/ijo.ijo_387_18
|View full text |Cite
|
Sign up to set email alerts
|

An unusual occurrence of stromal keratitis in dengue fever

Abstract: Dengue is a mosquito-borne infection endemic in the tropical and subtropical regions of the world. Classic dengue fever is a self-limiting, influenza-like illness transmitted by Aedes aegypti mosquito. Ophthalmic manifestations though rare can involve both the anterior and posterior segments and are usually associated with the thrombocytopenic state. However, ophthalmic complications such as anterior uveitis and vasculitis suggest immune-mediated pathogenesis. Herein, we report a rare case of stromal keratitis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…Whereas, in our study, there was a current history of fever and the platelet levels were >60,000/µl. Bawankar et al reported a case of stromal keratitis in dengue fever, in a 25-year-old female [15]. The patient developed stromal keratitis 15 days post dengue fever.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whereas, in our study, there was a current history of fever and the platelet levels were >60,000/µl. Bawankar et al reported a case of stromal keratitis in dengue fever, in a 25-year-old female [15]. The patient developed stromal keratitis 15 days post dengue fever.…”
Section: Discussionmentioning
confidence: 99%
“…Bawankar et al reported a case of stromal keratitis in dengue fever, in a 25-year-old female [ 15 ]. The patient developed stromal keratitis 15 days post dengue fever.…”
Section: Discussionmentioning
confidence: 99%
“…1 2 3 27 40 41 Panophthalmitis and anterior segment manifestations including anterior uveitis and stromal keratitis are less common. 42 43 …”
Section: R Esultsmentioning
confidence: 99%
“…Other posterior segment involvements include optic neuritis, neuroretinitis, central retinal artery occlusion, and exudative retinal detachment. 41 42 48 58 59 Although ocular manifestations typically have a benign clinical course, optic neuritis may result in permanent visual loss. Recently, recurrence in Chikungunya retinitis has been reported.…”
Section: R Esultsmentioning
confidence: 99%
“…Finally, a medical disorder might concurrently occur after COVID-19 vaccination. For example, dengue is reported in vaccine recipient [ 3 ] and stromal keratitis is also a possible rare clinical problem induced by dengue [ 4 ].…”
mentioning
confidence: 99%